Synthesis and characterisation of a new graphitic C–S compound obtained by high pressure decomposition of CS2. (15th November 2021) - Klotz, S.; Baptiste, B.; Hattori, T.; Feng, S.M.; Jin, Ch; Béneut, K.; Guigner, J.M.; Estève, I.
Abstract: Carbon disulphide (CS2 ) is, together with its closest analogue CO2, one of the simplest molecular systems made of double covalent bonds. Under high pressure, the molecular structure is expected to break up to form extended crystalline or polymeric solids. Here we show that by compression at 300 K to ∼10 GPa (100 kbar) using large-volume high pressure techniques, a sudden reaction leads to a mixture of pure sulphur and a well-defined compound with stoichiometry close to C2 S which can be recovered to ambient pressure. We present neutron and x-ray diffraction as well as Raman data which show that this material consists of sulphur bonded to sp 2 graphite layers of nanometric dimensions. The compound is a semiconductor with a gap of 45 meV, as revealed by temperature dependent resistivity measurements, and annealing at temperatures above 200 °C allows to reduce its sulphur content up to C10 S. Its structural and electronic properties are fundamentally different to "Bridgman black" reported from previous high pressure experiments on CS2 . Graphical abstract: Image 1